Kharif rice crop acreage and yield estimation using microwave and optical remote sensing time series satellite data: A case study of the eastern region of Maharashtra - Pritam Meshram; Kishan Singh Rawat; Gaurav Singh (Acta Scientiarum Polonorum. Formatio Circumiectus, 2024)
Aim of the study: The study aims to assess the feasibility of using remote sensing to estimate crop area and yield in a major rice-growing region of Maharashtra.